Medical Research Council Hot Topic workshop report: Planning a UK Nutrition and Healthy Life Expectancy Trial - Carter, J; Mathers, J; Fairweather‐Tait, S; Jebb, S; Sattar, N; Jennings, A; Minihane, A (British Nutrition Foundation, 2021)
There is a drive in the UK to harness findings from novel fundamental and efficacy nutritional research and, through inter-disciplinary and multi-agency collaborations, to improve eating behaviour for the benefit of population health. This report summarises the progress made during the Medical Research Council-funded Hot Topic workshop on the planning for a potential UK-wide nutrition primary prevention randomised controlled trial with incident disease as the study endpoint: the UK Nutrition and Healthy Life Expectancy (NuLifE) Trial. Through two workshops, along with online discussions and a systematic evidence synthesis, over 40 experts from a range of disciplines came together over 6 months. The workshop reached a consensus and delivered a three-stage plan with the ultimate ambitious aim of providing effective eating behaviour change strategies to address the growing inequalities in the UK and contribute to both a reduced risk of prevalent diet-related chronic disease and an increase in healthy life expectancy.